Technical and Economic Assessment of Off-grid, Mini-grid and Grid Electrification Technologies : Annex 1. Detailed Technology Descriptions and Cost Assumptions - World Bank (Washington, DC, 2014)
This report is part of the Energy and Water Department's commitment to providing new techniques and knowledge which complement the direct investment and other assistance to electrification as provided by the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA). The purpose of this report is to convey the results of an assessment of the current and future economic readiness of electric power generation alternatives for developing countries. The objective of the technical and economic assessment was to systematically characterize the commercial and economic prospects of renewable and fossil fuel-fired electricity generation technologies now, and in the near future. The study was designed to cover the widest possible range of electrification applications faced by energy services delivery and power system planners, whether supply is provided through grid networks or stand-alone or mini-grid configurations. The assessment was conducted using a standard approach and is presented in a consistent fashion for each power generation technology configuration. The assessment time frame includes current status and forecast development trends over the period 2005-15, while the economic assessment considers a range of typical operating conditions (peak, off-peak) and grid configurations (off-grid, mini-grid, interconnected grid) for various scales of demand. The technology characterization reflects the current stage of commercialization, including indicative cost reduction trends over 10 years. This study is limited in several ways. First, it is time-bound. It does not reflect new technology developments or new secular trends that have emerged since the terms of reference were formalized. Secondly, it is bound by the available literature. Thirdly, the results are generalized and represent averaging over what are important specific conditions (although the uncertainty analysis accounts for this somewhat).